2020
DOI: 10.3390/cancers12020430
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Exon 15 Mutations in Papillary Carcinoma and Adjacent Thyroid Parenchyma: A Search for the Early Molecular Events Associated with Tumor Development

Abstract: BRAF exon 15 mutations are the most common molecular alterations found in papillary thyroid carcinoma (PTC). To date, there is no information regarding BRAF alterations in the thyroid parenchyma surrounding the tumor. To explore the early events associated with the development of PTC, we used massively parallel sequencing to investigate BRAF exon 15 in 30 PTCs and in 100 samples from the thyroid parenchyma surrounding the tumor. BRAF p.V600E was identified in 19/30 PTCs (63.3%). BRAF p.V600E mutations were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“… † Lies within protein kinase domain of the Braf protein but actual effect on protein function remains unknown 36 . ‡ Two point mutations at codon 558 (AAG to AAT) and codon 559 (GTT to ATT).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… † Lies within protein kinase domain of the Braf protein but actual effect on protein function remains unknown 36 . ‡ Two point mutations at codon 558 (AAG to AAT) and codon 559 (GTT to ATT).…”
Section: Resultsmentioning
confidence: 99%
“…† Lies within protein kinase domain of the Braf protein but actual effect on protein function remains unknown 36 .…”
Section: Resultsmentioning
confidence: 99%
“…The tumor was genetically IDH wild‐type/H3 wild‐type but harbored the rare BRAF A598T mutation. BRAF A598T mutation has been reported in lung adenocarcinoma 16 and thyroid tissue adjacent to the papillary thyroid carcinoma 17 but never previously in gliomas. BRAF is an important member of the MAPK pathway, and BRAF V600E is the most common cancer‐associated mutation.…”
Section: Discussionmentioning
confidence: 93%
“…BRAF V600E mutation is related to a gain‐of‐function effect of a protein and induces constitutive activation of the MAPK pathway, resulting in dysregulated cell proliferation and growth. In contrast, BRAF A598T mutation is predicted to induce a loss‐of‐function effect of a kinase (http://www.jax.org, 17,18 ). Tumorigenesis of a BRAF ‐inactivating mutation has recently been reported 19–22 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, their data indicated that a mutagenic process affecting BRAF exon 15 takes place in a subset of thyroid glands that develop BRAF p.V600E mutated PTCs. While the carcinoma develops only if the p.V600E mutation occurs, its development is accompanied by other exon 15 mutations [ 2 ]. Fugazzola et al reviewed the data in favor of the occurrence of intratumoral heterogeneity in PTC and reasoned on its impact on prognosis and on the response to targeted therapy [ 3 ].…”
mentioning
confidence: 99%